2001
DOI: 10.1080/00074910152669181
|View full text |Cite
|
Sign up to set email alerts
|

Small and Medium Enterprise Dynamics in Indonesia

Abstract: This paper discusses the development of small and medium enterprises (SMEs) in Indonesia before and during the crisis. It argues that SME productivity has risen substantially, at rates not far from those of larger firms. Case studies indicate that various mechanisms are at work, such as technology diffusion through foreign buyers and subcontracting. The prevalence of SME clusters suggests that they benefit small and medium enterprise development. SMEs are found to have been weathering the crisis better than la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 14 publications
1
76
1
16
Order By: Relevance
“…Large enterprises may be the first to lay-off workers in order to reduce operational costs to thrive the crisis. Berry et al (2001) and Tan and See (2004) also found evidence on SMEs' resistance during volatile macroeconomic conditions. Nevertheless, the effect of size is less visible among FFs, as large FFs' employment growth rates did not evolve significantly different from that of smaller FFs during the two recessions (Model A.5).…”
Section: Employment Growthmentioning
confidence: 96%
“…Large enterprises may be the first to lay-off workers in order to reduce operational costs to thrive the crisis. Berry et al (2001) and Tan and See (2004) also found evidence on SMEs' resistance during volatile macroeconomic conditions. Nevertheless, the effect of size is less visible among FFs, as large FFs' employment growth rates did not evolve significantly different from that of smaller FFs during the two recessions (Model A.5).…”
Section: Employment Growthmentioning
confidence: 96%
“…As a result, SMEs may be more able to sustain their employment levels and thus counteract the negative effects of the crisis, helping to stabilize the economy. Indeed, there is robust empirical evidence showing that SMEs, and specifically export-oriented SMEs, are better able to adjust to crises (e.g., Sato 2000;Berry et al 2001;and Wengel and Rodriguez 2006 There are also several reasons to expect smaller firms to be more vulnerable to the negative effects of an economic crisis. On the one hand, SMEs may suffer disproportionately from economic downturns due to their limited financial resources and dependence on banks' lending, paying for such high interest rates (e.g.…”
Section: Firm Size Firm Growth and Economic Downturnsmentioning
confidence: 99%
“…Smaller enterprises may be more flexible in adapting to an economic downturn as they are less resistant to inertia, rigidity and sunk costs (Tan and See 2004), more able to exploit market niches (Gregory et al 2002;Narjoko and Hill 2007;Hodorogel 2009), being concentrated on activities characterized by economies of agglomeration, rather than economies of scale (Berry et al 2001;Hall and Harvie 2003), and less reliant on formal credits compared to their larger counterparts, who are more burdened by debts (Sato 2000;Wangel and Rodriguez 2006). Even their disadvantages at technological and knowledge levels can be overcome through the imitation of other firms' best practices (Nugent and Yhee 2002).…”
Section: Firm Size Firm Growth and Economic Downturnsmentioning
confidence: 99%
“…For instance, Berry, Rodriguez and Sandee (2001) reported that micro and small manufacturing enterprises in Indonesia employ 67 percent of the total working population in the country in manufacturing establishments. Similarly, in Ghana, micro, small and medium-sized enterprises are said to be a characteristic feature of the production landscape and have been noted to provide about 85 percent of manufacturing employment of Ghana (Abor & Quartey, 2010).…”
Section: Introductionmentioning
confidence: 99%